Sustainable education: A buzzword of universiti teknologi PETRONAS, Malaysia - Zahid, M. (IGI Global, 2016)
The sustainable development (hereafter, S.D.) aims a growth that could satisfy the wants and needs ofpresent generation without affecting future generations. Accordingly, this study investigates the role ofHEIs in S.D. by selecting the case of Universiti Teknologi PETRONAS, Malaysia. The study adapted theuniversities sustainable development initiatives checklist/index for qualitative analysis of the main website,operational documents, and practical initiatives of the university for S.D. The findings revealed that theuniversity has good and meaningful contributions towards three dimensions of S.D. i.e. economic, socialand environment. The study proposed an improvement in Education for Sustainable Development (ESD)and implementation of S.D. framework for universities. The findings have significance and practical implicationsfor academia, regulatory bodies, policy makers, and HEIs. Also, the findings are significantin association with new economic model (NEM) and vision 2020 of Malaysia. Â© 2017 by IGI Global. All rights reserved.